2021
DOI: 10.1002/ccr3.4407
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab induced cytokine release syndrome in an MS patient: A case report

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This method involves gradually administering increasing doses of the drug [7,8]. Rapid IgE desensitization inhibits IL-6 [8], and studies [9] showed a 75% reduction in IL-6 production post-desensitization.…”
Section: Introductionmentioning
confidence: 99%
“…This method involves gradually administering increasing doses of the drug [7,8]. Rapid IgE desensitization inhibits IL-6 [8], and studies [9] showed a 75% reduction in IL-6 production post-desensitization.…”
Section: Introductionmentioning
confidence: 99%